Fasting plasma triglycerides predict the glycaemic response to treatment of Type 2 diabetes by gastric electrical stimulation. A novel lipotoxicity paradigm. Issue 6 (7th March 2013) - Lebovitz, H. E.; Ludvik, B.; Yaniv, I.; Haddad, W.; Schwartz, T.; Aviv, R.; ,
Abstract Background Non‐stimulatory, meal‐mediated electrical stimulation of the stomach (TANTALUS‐DIAMOND) improves glycaemic control and causes modest weight loss in patients with Type 2 diabetes who are inadequately controlled on oral anti‐diabetic medications. The magnitude of the glycaemic response in clinical studies has been variable. A preliminary analysis of data from patients who had completed 6 months of treatment indicated that the glycaemic response to the electrical stimulation was inversely related to the baseline fasting plasma triglyceride level. Method An analysis of 40 patients who had had detailed longitudinal studies for 12 months. Results Twenty‐two patients with fasting plasma triglycerides ≤ 1.7 mmol/l had mean decreases in HbA1c after 3, 6 and 12 months of gastric contraction modulation treatment of −15 ± 2.1 mmol/mol (−1.39 ± 0.20%), −16 ± 2.2 mmol/mol (−1.48 ± 0.20%) and −14 ± 3.0 mmol/mol (−1.31 ± 0.26%), respectively. In contrast, 18 patients with fasting plasma triglyceride > 1.7 mmol/l had mean decreases in HbA1c of −7 ± 1.7 mmol/mol (−0.66 ± 0.16%), −5 ± 1.6 mmol/mol (−0.44 ± 0.18%) and −5 ± 1.7 mmol/mol (−0.42 ± 0.16%), respectively. Pearson's correlation coefficient between fasting plasma triglyceride and decreases in HbA1c at 12 months of treatment was 0.34 (P < 0.05). Homeostasis model assessment of insulin resistance was unchanged during 12 months of treatment in patients with high baseline fasting triglycerides, while it progressively improved in patients with low fasting plasma triglycerides. Patients with low fasting plasma triglycerides had a tendency to lose more weight than those with high fasting plasma triglycerides, but this did not achieve statistical significance. Conclusions The data presented suggest the existance of a triglyceride lipotoxic mechanism that interferes with gastric/neural mediated pathways that can regulate glycaemic control in patients with type 2 diabetes. The data suggest the existence of a triglyceride lipotoxic pathway that interferes with gastric/neural mediated pathways that can regulate glycaemic control.